The use of butane diacetals of glycolic acid as precursors for the synthesis of the phytotoxic calmodulin inhibitor herbarumin II - Diez, E; Dixon, D; Ley, S; Polara, A; Rodriguez, F (2003)
The total synthesis of phytotoxic nonenolide herbarumin II (1) has been achieved by implementation of butane diacetal (BDA)-desymmetrised glycolate building blocks. Three of the four stereogenic centres present in the key coupling fragments were generated from both enantiomeric forms of the BDA building block in highly diastereoselective alkylation and aldol reactions.